2011
DOI: 10.1111/j.1439-0507.2009.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal effect of photodynamic therapy against fluconazole-resistant Candida albicans and Candida glabrata

Abstract: SummaryAlthough photodynamic therapy (PDT) has shown great promise for the inactivation of Candida species, its effectiveness against azole-resistant pathogens remains poorly documented. This in vitro study describes the association of Photogem Ò (Photogem, Moscow, Russia) with LED (light emitting diode) light for the photoinactivation of fluconazole-resistant (FR) and American Type Culture Collection (ATCC) strains of Candida albicans and Candida glabrata. Suspensions of each Candida strain were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 48 publications
11
107
2
5
Order By: Relevance
“…The level of variation within the same species was more pronounced in the planktonic cultures exposed to PDT, but biofilms also showed significant discrepancies. Significant differences observed in the present study among Candida species and strains with regard PDT susceptibility also concur with previous studies [15,32,39]. Therefore this investigation once again confirms the importance of testing more than one isolate of Candida belonging to a given species to characterize the species-specific behavior.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The level of variation within the same species was more pronounced in the planktonic cultures exposed to PDT, but biofilms also showed significant discrepancies. Significant differences observed in the present study among Candida species and strains with regard PDT susceptibility also concur with previous studies [15,32,39]. Therefore this investigation once again confirms the importance of testing more than one isolate of Candida belonging to a given species to characterize the species-specific behavior.…”
Section: Discussionsupporting
confidence: 92%
“…C. glabrata required a higher CUR concentration to achieve 4 log reduction in CFU/ml counts and it was not completely inactivated in any of the protocols tested. Other investigations also found the reduced susceptibility of C. glabrata suspensions to photoinactivation [14,15]. However, this reduced susceptibility was not observed in C. glabrata biofilms, which showed similar levels of photoinactivation in comparison with C. albicans biofilms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…20,37 Moreover, on epithelial surfaces C. albicans grows as a biofilm, 38 which is less susceptible to PDT than its planktonic counterpart. 24,28 It has been suggested that incomplete kill of PDT on biofilms might be because of the failure of PS and light penetration into the inner regions of the biofilm. 39,40 Thus, in comparison with these in vitro studies, the higher PS concentrations and light fluence required for photoinactivation in the present investigation may be explained by the physiological responses of C. albicans to the in vivo environment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study showed that PDT mediated by Photogem and blue LED light resulted in complete inactivation of planktonic suspensions and significant reduction in biofilm viability. 28 However, in vivo application of antimicrobial PDT using porphyrins and LED light has not yet been well established and animal models may provide outcomes more closely correlated to clinical situations. Thus, the aim of the present investigation was to contribute to in vivo antimicrobial PDT development by reporting on the photoinactivation of C. albicans in a murine model of oral candidosis using a porphyrin in association with LED light sources of different wavelengths.…”
mentioning
confidence: 99%